Angiotensin II receptor I blockade prevents stenosis of tissue engineered vascular grafts. Issue 12 (15th June 2018) - de Dios Ruiz‐Rosado, Juan; Lee, Yong‐Ung; Mahler, Nathan; Yi, Tai; Robledo‐Avila, Frank; Martinez‐Saucedo, Diana; Lee, Avione Y.; Shoji, Toshihiro; Heuer, Eric; Yates, Andrew R.; Pober, Jordan S.; Shinoka, Toshiharu; et al.
ABSTRACT: We previously developed a tissue‐engineered vascular graft (TEVG) made by seeding autologous cells onto a biodegradable tubular scaffold, in an attempt to create a living vascular graft with growth potential for use in children undergoing congenital heart surgery. Results of our clinical trial showed that the TEVG possesses growth capacity but that its widespread clinical use is not yet advisable due to the high incidence of TEVG stenosis. In animal models, TEVG stenosis is caused by increased monocytic cell recruitment and its classic ("M1") activation. Here, we report on the source and regulation of these monocytes. TEVGs were implanted in wild‐type, CCR2 knockout ( Ccr2 −/− ), splenectomized, and spleen graft recipient mice. We found that bone marrow—derived Ly6C +hi monocytes released from sequestration by the spleen are the source of mononuclear cells infiltrating the TEVG during the acute phase of neovessel formation. Furthermore, short‐term administration of losartan (0.6 g/L, 2 wk), an angiotensin II type 1 receptor antagonist, significantly reduced the macrophage populations (Ly6C +/− /F480 + ) in the scaffolds and improved long‐term patency in TEVGs. Notably, the combined effect of bone marrow‐derived mononuclear cell seeding with short‐term losartan treatment completely prevented the development of TEVG stenosis. Our results provide support for pharmacologic treatment with losartan as a strategy to modulate monocyte infiltration into the grafts and thus prevent TEVG stenosis.—Ruiz‐Rosado, J. D. D., Lee, Y.‐U., Mahler, N., Yi, T., Robledo‐Avila, F., Martinez‐Saucedo, D., Lee, A.Y., Shoji, T., Heuer, E., Yates, A.R., Pober, J. S., Shinoka, T., Partida‐Sanchez, S., Breuer, C. K. Angiotensin II receptor I blockade prevents stenosis of tissue engineered vascular grafts. FASEB J. 32, 6822‐6832 (2018). www.fasebj.org